Al-Maṣdar al-Muawwal fī al-Naṣṣ al-Qurʾānī bayna al-I’rāb wa al-Ta’wīl: Qirā’ah fī Juhūd al-Mufassirīn - Saputri, Nike; Yandi, Elfi; Hanomi, Hanomi (HuRuf Journal : International Journal of Arabic Applied Linguistic, 2025)
This study presents an analytical investigation of the al-maṣdar al-muʾawwal (the nominalized clause) in the Qur'anic text from the perspectives of grammatical analysis (I’rāb) and interpretation (ta’wīl), focusing on how the variety of its syntactic functions directly influences the diversity of exegetical meanings. The research is based on the hypothesis that the multiplicity of grammatical roles played by this construction contributes significantly to the richness of its interpretative dimensions. The aim of this study is to explore the relationship between the syntactic analyses provided by Qur'anic exegetes and the various interpretations derived from these analyses in understanding the meanings of the verses. The researcher adopts a descriptive-analytical approach by examining instances of al-maṣdar al-muʾawwal in selected Qur'anic verses and comparing the views of prominent exegetes. The findings reveal that the nominalized clause serves not only a grammatical function but also plays a significant interpretative role in shaping meaning and identifying rhetorical intentions. The study concludes that integrating grammatical analysis with interpretation is essential for a deeper understanding of the Qur'anic text and for appreciating its linguistic eloquence. يتناول هذا البحث دراسةً تحليليةً للمصدر المؤول في النص القرآني من حيث الإعراب والتأويل، مع التركيز على تأثير تنوع الوظائف النحوية لهذا التركيب على دلالاته التفسيرية، تنطلق الدراسة من فرضية مفادها أن تعدد الوظائف النحوية للمصدر المؤول يؤثر تأثيرًا مباشرًا في تعدد معانيه التفسيرية، تهدف هذه الدراسة إلى الكشف عن العلاقة بين التحليل النحوي الذي قدمه المفسرون لهذا المصدر والتأويلات التي نتجت عن هذه التحليلات في فهم معاني الآيات، وقد اعتمدت الباحثة في دراسته على المنهج التحليلي الوصفي من خلال استقراء مواضع المصدر المؤول في بعض الآيات القرآنية ومقارنة آراء المفسرين، أظهرت النتائج: أن المصدر المؤول ليس له دور نحوي فقط، بل يعد عنصرًا تأويليًا يؤثر في توجيه المعنى وتحديد المقاصد البلاغية، وتخلص الدراسة إلى أن الجمع بين الإعراب والتأويل هو أسلوب ضروري لفهم أعمق للنص القرآني ولإبراز بلاغته اللغوية.